Bimetallic Pairs Supported on Graphene as Efficient Electrocatalysts for Nitrogen Fixation: Search for the Optimal Coordination Atoms. Issue 14 (8th June 2020) - Hu, Riming; Li, Yongcheng; Zeng, Qingwen; Wang, Fuhe; Shang, Jiaxiang
Abstract: The electrocatalytic nitrogen reduction reaction (NRR) is a most attractive approach to ammonia synthesis, and the development of catalysts with excellent activity, high NRR selectivity, and long‐term durability is crucial but remains a great challenge. Herein, by means of density functional theory calculations, the stability and catalytic performance of anchored bimetals was systematically investigated by pairing different transition‐metal atoms (Mo, Cr, Ti, V, Ru, and W) on graphene with different coordination atoms (C, N, O, P, and S) for N2 fixation. By screening the stability, limiting potential, and selectivity of 105 candidates, carbon was found to be the optimal coordination atom for bimetallic pairs, whereas the other four coordination atoms were unsatisfactory owing to either thermodynamically unstable anchor sites for bimetallic pairs (O, P, and S atoms) or relatively low catalytic activity (N atom). Notably, the bimetallic compound of Mo and Ti supported on C‐coordinated graphene (MoTi‐CG) and TiV‐CG were predicted as effective NRR catalysts with the attractive limiting potentials of −0.34 and −0.30 V. Furthermore, the volcano curve between the limiting potential and the adsorption free energy of NH2 * [Δ G (NH2 *)] was revealed, in which a moderate Δ G (NH2 *) was required for high‐activity NRR catalysts. This study not only provides a theoretical basis for the rational design of bimetallic compounds anchored on graphene as effective NRR catalysts under ambient conditions but also opens up a new way to accelerate the screening of NRR catalysts. Abstract : Bi and large : Carbon is predicted to be the optimal coordination atom for bimetallic pairs supported on graphene to achieve high stability, excellent activity, and outstanding selectivity for nitrogen fixation through the electrocatalytic nitrogen reduction reaction.